UJI EFIKASI KELAMBU BERINSEKTISIDA DI DESA SUMARE KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Anis Nurwidayati; Andi Arahmadani Arasy (SPIRAKEL, 2019)
One of malaria control methods is by prevention of vector control by using insecticide. One of them is the long-lasting Insecticidal nets (LLINs). The use of LLINs is chosen because it is easy to apply and lasts longer (approximately three years). However, uncontrolled and continuous use will triggers the resistance of mosquitoes to insecticides present in mosquito nets. The test activity aimed to determine the effectiveness of LLINs in Sumare Village. Testing was conducted by following WHO standard method. The results showed that LLINs with permethrin active ingredient in 2012 were no longer effective to be used, with the mortality rate of Anopheles subpictus mosquitoes only 36%. Testing of active LLINs delthamethrin procurement in 2014 was also not effective with Anopheles subpictus mosquito mortality rate of 61.4%. Average temperature recorded during the test was 29C and relative humidity of 72%. The conclusion is the LLINs in Sumare Village that used for one up to three years was not effective.